Adsorption of Heavy Metal Ions (Cr3+ and Cu2+) from Aqueous Solution using HCl Modified Water Hyacinth as Low-Cost Bioadsorbent - Kamboj, Vishal; Tiwari, D.P. (Asian Journal of Chemistry, 2022)
In present study, the HCl modified water hyacinth (WH) dried powder as bioadsorbent is utilized for removing heavy metal Cr3+ and Cu2+ ions from the aqueous solutions. Different techniques were applied for testing the adsorbent properties of the prepared bioadsorbent such as X-ray diffraction (XRD), Thermo-gravimetric analysis (TGA), X-ray fluorescence (XRF), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). In this study, the prepared bioadsorbent was evaluated for five different metal inlet concentrations (0.5, 1, 1.5, 2 and 3 mg/L) and 30-120 min time period. The batch adsorption study findings indicated that the maximum metal removal percentage (sorption percentage) was observed at 0.5 mg/L concentration and 120 min. In addition, the batch experiment observations also revealed that the Cr3+ adsorption capacity is higher than Cu2+ (removal% for Cr3+ is 94.75%, while for Cu2+ is 91.10%) at 120 min and 0.5 mg/L inlet concentration. This greater adsorption capabilities of heavy metals removal were due to the uniform dispersion of the various elements (Cl, K, Ca, Na, P, S, Si and Mg) confirmed by SEM-EDS as well as XRF and the retained basic cellulosic structure of water hyacinth confirmed by XRD studies even after using HCl acid.